OKF-Ref: using the object knowledge framework to understand the reference experience. Issue 2 (15th February 2016) - Latham, Kiersten F.; Kearns, Jodi
Abstract : Purpose: – The aim of this paper is to offer a platform for thinking about the reference interaction experience by borrowing from museum studies literature, particularly from a holistic understanding of the museum visitor's experience. Design/methodology/approach: – The goal of this paper is to offer a platform for thinking about the reference interaction experience by borrowing from museum studies literature, particularly from a holistic understanding of the museum visitor's experience. Findings: – Object knowledge framework-reference (OKF-Ref) enables reference staff to connect patrons with resources to enable deeper thinking and research. Practical implications: – OKF-Ref seeks to permit reference transactions as experiences rooted in synchronous individual, group and material potential connections made between resources and information seekers. Originality/value: – New considerations in lived reference experience encourages reference librarians to think about the whole experience of reference interactions, allowing intermediaries to be proactive toward the goal of unified experiences for patrons.